KAJIAN EMPIRIS BEBAN PAJAK TANGGUHAN DAN KEPEMILIKAN INSTITUSIONAL TERHADAP MANAJEMEN LABA - - Reskino; Issan Chairul Imam (Universitas Trunojoyo Madura, 2016)
This study is aimed to investigate the influence of deferred tax and institusional ownership on earning management. This research used the sample of manufactur industries listed in Indonesian Stock Exchange during 2010-2013 period. The number of manufactur industries sampled in this study were 78 companies with 4 years observation. Based on purposive sampling method, sample consist of 312 financial statement in this research. Hypothesis in this research are tested by logistic regression analytical method.Based on sample, the result show that deferred tax negative-significantly influence to earning management and institusional ownership negative-significantly influence to earning management.